2018
DOI: 10.1186/s41110-018-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Resistin and visfatin concentrations are related to central obesity and inflammation in Brazilian children

Abstract: Background: The evidence that cardiovascular disease begins in childhood and adolescence, especially in the presence of excess weight, is associated with dysfunction on adipokine pro-inflammatory secretion. These affect glucose metabolism and lead to other complications related to insulin resistance and cardiovascular disease. This study assessed the association of anthropometric and metabolic parameters related to obesity, cardiovascular risk, and insulin resistance with concentrations of resistin and visfati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(68 reference statements)
1
3
1
Order By: Relevance
“…Similarly, this present study revealed positive correlations between visfatin and FBS in addition to HOMA-IR in both obese children and obese adolescents' groups. In contrast to previous findings obtained in obese children, a study by Simões et al [23] has shown visfatin negatively associated with HOMA-IR but this current study showed positive correlation between these two variables. The association between circulating visfatin and the parameters of glucose homeostasis and insulin resistance remains controversial due to contradicting data [24] [25] potentially due to the differences in immunoassay specificity [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, this present study revealed positive correlations between visfatin and FBS in addition to HOMA-IR in both obese children and obese adolescents' groups. In contrast to previous findings obtained in obese children, a study by Simões et al [23] has shown visfatin negatively associated with HOMA-IR but this current study showed positive correlation between these two variables. The association between circulating visfatin and the parameters of glucose homeostasis and insulin resistance remains controversial due to contradicting data [24] [25] potentially due to the differences in immunoassay specificity [26].…”
Section: Discussioncontrasting
confidence: 99%
“…The findings obtained with the current study showed higher mean serum visfatin level for the recruited thalassemic patients (average value of 7.1 ng/mL and a range of 1.9-13.4 ng/mL) than that reported in the literature for normal weight healthy children (average value of 2.19 ng/mL and a range of 1.4-3.26 ng/mL). 38 The current results come in line with previous studies postulated higher level of adipocytokines notably visfatin among patients with b-thalassemia. It also indicates the possible inflammatory role of visfatin in this condition, the possible association of this adipocytokine with endothelial and vascular dysfunction in patients with b-thalassemia, and its correlation with disease severity.…”
Section: Discussionsupporting
confidence: 93%
“…Dobiasova et al, (19) pointed AIP to be the significant predictor of cardiovascular risk for both research and for practice. Simões et al,(20) also demonstrated the atherogenic index of plasma as the best marker of atherosclerosis in their studies.…”
Section: Discussionmentioning
confidence: 93%